Greening the future of healthcare: implementation of sustainability strategies in German hospitals and beyond—a review - Schwab, Roxana; Schiestl, Lina Judit; Hasenburg, Annette (Frontiers in Public Health, 2025)
This study explores the implementation of sustainability measures within German hospitals, emphasizing their critical role in mitigating environmental impacts and promoting public health. The healthcare sector significantly contributes to global greenhouse gas emissions, necessitating urgent reforms in energy use, waste management, construction, transportation, and food systems. Key findings highlight the potential for hospitals to enhance energy efficiency, adopt renewable energy sources, and reduce waste through innovative technologies and sustainable practices. Initiatives such as green hospital designs, climate-conscious food systems, and sustainable procurement strategies are central to reducing the ecological footprint. Despite these opportunities, barriers such as workforce shortages, insufficient funding, and technical complexity hinder progress. Addressing these challenges through leadership commitment, resource allocation, and staff engagement is essential for aligning the healthcare sector with national and international sustainability goals. By prioritizing sustainability, hospitals can achieve long-term economic benefits, improve patient outcomes, and foster a healthier, more resilient society.